Assessment of depression among chronic obstructive pulmonary disease (COPD) patients at rural tertiary care centre of Northern India - Gautam, Aditya Kumar; Kumar, Adesh; Gupta, Ashish Kumar; Kushwaha, Bal Krishna; Yadav, Prashant; Pandey, Achyut Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Chronic obstructive pulmonary disease COPD is a more complex systemic disease that has significant extra pulmonary effects along with pulmonary involvement. Complexity and mortality of COPD is increased by its co-morbidities and exacerbations. Depression is One of the commonest co-morbidity that occurs in patient with COPD and is associated with poor quality of life therefore we planned to assess depression among COPD patients. Methods: This was a cross-sectional study done in the respiratory medicine department of tertiary care centre, during the period from January 2015 to June 2016. A total of 200 patients of COPD of either sex having age more than 40 years included in the study. Patients who were critically ill and uncooperative excluded from the study. Patients who did not give consent and having previous history of any psychiatric illness also excluded from the study. The diagnosis of COPD was made on the basis of the clinical history, examination, X-ray chest and spirometry. Further, depression was evaluated with the validated Hindi version of nine items PHQ-9 (a subset of patient health questionnaire). Results: The data of all 200 COPD patients were analysed and it was observed that- prevalence of depression in COPD was found to be 49%. Prevalence was higher in male patients 147 (73.5%) as compared to female 53 (26.5%) patients in the present study. Minimal depression was found in 14.28 % COPD patients and mild depression in 25.51 % moderate depression in 39.79 % cases and severe depression in 20.40% cases. Conclusions: Symptoms of depression are common in patients with COPD and its presence may have significant impact on the quality of life of such patients and may be associated with a higher mortality rate.